Biogem: An effective tool-based approach for scaling up open source software development in bioinformatics - Bonnal, R.; Aerts, J.; Githinji, G.; Goto, N.; Maclean, D.; Miller, C.; Mishima, H.; Pagani, M.; Ramirez-gonzalez, R.; Smant, G.; Strozzi, F.; Syme, Robert; et al. (2012)
Summary: Biogem provides a software development environment for the Ruby programming language, which encourages community-based software development for bioinformatics while lowering the barrier to entry and encouraging best practices. Biogem, with its targeted modular and decentralized approach, software generator, tools and tight web integration, is an improved general model for scaling up collaborative open source software development in bioinformatics. © The Author(s) 2012. Published by Oxford University Press.